COMMUNITY SERVICE, EDUCATION, PREVENTION AND EARLY MANAGEMENT OF POSTPARTUM BLEEDING IN HIGH-RISK PREGNANCIES AT SALLY CLINIC - Deni Irawati; Noer Desmie; Winda Azhari (Cattleya Darmaya Fortuna, 2024)
Maternal mortality (MMR) is still a major health challenge in Indonesia, with postpartum bleeding as one of the main causes. This Community Service (PkM) activity aims to increase the understanding of pregnant women at high risk at Sally Clinic regarding the danger signs and the initial steps of handling postpartum bleeding independently. The implementation of the activity was carried out on March 21, 2024 by a team of lecturers and students from STIKes Darmo Medan through an educational and structured health counseling method. The results of the activity showed a significant increase in participants' health literacy, where pregnant women and their families became more prepared and able to take preventive and responsive actions in dealing with emergencies. In conclusion, continuous education is a crucial strategy in efforts to reduce maternal mortality and improve patient safety standards in the Sally Clinic environment.